Consensus Statement of the International Summit on Intellectual Disability and Dementia Related to Nomenclature - Janicki, Matthew P.; McCallion, Philip; Splaine, Michael; Santos, Flavvia H. [UNESP]; Keller, Seth M.; Watchman, Karen (Amer Assoc Intellectual Developmental Disabilities, 2017)
A working group of the 2016 International Summit on Intellectual Disability and Dementia was charged to examine the terminology used to define and report on dementia in publications related to intellectual disability (ID). A review of related publications showed mixed uses of terms associated with dementia or causative diseases. As with dementia research in the non-ID population, language related to dementia in the ID field often lacks precision and could lead to a misunderstanding of the condition(s) under discussion, an increasingly crucial issue given the increased global attention dementia is receiving in that field. Most articles related to ID and dementia reporting clinical or medical research generally provide a structured definition of dementia or related terms; social care articles tend toward term use without definition. Toward terminology standardization within studies/reports on dementia and ID, the Summit recommended that a consistent approach is taken that ensures (a) growing familiarity with dementia-related diagnostic, condition-specific, and social care terms (as identified in the working group's report); (b) creating a guidance document on accurately defining and presenting information about individuals or groups referenced; and (c) using definitions and data, such as subjects' ages, sex, level of ID, residential situation, basis for dementia diagnosis, presence of Down syndrome (or other risk conditions), years from diagnosis, and if available, scores on objective measures of changing function, in reports on neuropathologies or cognitive decline or impairment.
Keywords: Alzheimer's; dementia; intellectual disability; nomenclature; terminology